When Science Meets Responsibility: The Major Risks Commission and the L'Aquila Earthquake. (June 2014) - Simoncini, Marta
Abstract : This article aims to analyse the role of law in the identification of the responsibility domain of 'regulatory science' (Jasanoff, 1990) within the risk regulatory process. The main research question is therefore, what kindof relationshipbetween science andpolicy-making lawshould design in risk regulation. In order to address this issue, this contribution focuses on the recent verdict of the Tribunal of L'Aquila. After the earthquake occurred in L'Aquila on the 6 th April 2009, six Italian scientists that had participated in the Major Risks Commission's meeting have been condemned for the multiple manslaughter of 29 people who were among the 309 victims of the earthquake, 'for having assessed the risks related to seismic activity in the L'Aquila territory in an inaccurate, generic and ineffective way' and for having provided 'information which was imprecise, incomplete and contradictory as to the nature, the causes and the hazardousness and on the future development of the seismic activity'. As far as risk assessment and risk communication are concerned, firstly the tasks of the Major Risks Commission under the Italian Civil Protection law will be analysed. Against this backdrop, the issues related to this expert body's responsibility will be addressed and the gaps in the current accountability regime will be pointed out.